ANALISIS PRICE BOOK VALUE DAN RETURN ON EQUITY SERTA DEVIDEN PAYOUT RATIO TERHADAP PRICE EARNING RATIO - Herry Ramadhani (FORUM EKONOMI, 2016)
This study aims to provide empirical evidence about the factors that affect the price earning ratio (PER) . This study aimed to analyze the Price Book Value (PBV) , Return on Equity ( ROE), Dividend Payout Ratio ( DPR ) to the Price Earning Ratio ( PER ) study on PT.Bank Mandiri,Tbk Year 2013 to 2015. Data used is secondary data by type of descriptive analysis research. From the analysis of data obtained from PT. Bank Mandiri Tbk concluded bawha from Price Book Value ( PBV ) , Return on Equity ( ROE ) , Dividend Payout Ratio ( DPR ) and the Price Earning Ratio ( PER ) PT.Bank Independent concludes that that the variable Price Book Value ( PBV ) , Return on Equity ( ROE ) , Dividend Payout Ratio ( DPR ) relating Price Earning Ratio ( PER ) in making investment decisions made by investorsKeyword: Price Book Value (PBV), Return On Equity (ROE), Deviden Payiut Ratio (DPR) dan Price Earning Ratio (PER)